2020
DOI: 10.3390/ijms21093344
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Blood–Brain Barrier Dysfunction in Traumatic Brain Injury

Abstract: Traumatic brain injuries (TBIs) account for the majority of injury-related deaths in the United States with roughly two million TBIs occurring annually. Due to the spectrum of severity and heterogeneity in TBIs, investigation into the secondary injury is necessary in order to formulate an effective treatment. A mechanical consequence of trauma involves dysregulation of the blood–brain barrier (BBB) which contributes to secondary injury and exposure of peripheral components to the brain parenchyma. Recent studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
119
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(139 citation statements)
references
References 225 publications
(296 reference statements)
0
119
0
Order By: Relevance
“…Therefore, in this study we observed dysfunction of hippocampal neurons caused by AQP4-induced brain edema. The hippocampus is the key area for spatial learning and memory, and it plays an important role in spatial navigation, goal-oriented tasks and memory storage [ 28 ]. Our results showed that neuronal loss and cerebral swelling were severe after TBI, and the level of MAP2, an important component of dendritic markers and neuronal cytoskeleton in the hippocampus, significantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in this study we observed dysfunction of hippocampal neurons caused by AQP4-induced brain edema. The hippocampus is the key area for spatial learning and memory, and it plays an important role in spatial navigation, goal-oriented tasks and memory storage [ 28 ]. Our results showed that neuronal loss and cerebral swelling were severe after TBI, and the level of MAP2, an important component of dendritic markers and neuronal cytoskeleton in the hippocampus, significantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanisms by which acute CNS injury disrupts the BBB in the setting of TBI is debatable; however, acute hypertension, hyperosmolar solutions, classical inflammation, enhanced para/transcellular transport, and enhanced activity of matrix metalloproteinases (MMPs) have all been implicated, among many others [ 147 ]. Such alterations in barrier permeability following acute CNS injury arise due to loss or alterations in the function of key structural and functional components, which has major implications for injury progression and outcome [ 148 ]. The poor recovery and high mortality of TBI are largely attributable to the development of cerebral edema and elevated intracranial pressure (ICP).…”
Section: Tbi-related Ultrastructural Damage To Blood–brain Barriermentioning
confidence: 99%
“…The poor recovery and high mortality of TBI are largely attributable to the development of cerebral edema and elevated intracranial pressure (ICP). These serious downstream complications are closely related to the loss of structural integrity and permeability of BBB after TBI [ 148 ]. The bioenergetic crisis that ensues following TBI as a result of secondary injury processes leads to a lack of ATP production, and this leads to failure of the Na + /K + -ATPase pump, essential for the maintenance of ion homeostasis [ 149 ], which results in an inability to maintain ionic gradients across the membrane and leads to intracellular accumulation of sodium.…”
Section: Tbi-related Ultrastructural Damage To Blood–brain Barriermentioning
confidence: 99%
“…To struggle for clear understanding on TBI, even nowadays, there still remain controversaries that if any model could appropriately mimic the complex process in vivo 4 , 23 . The primary injury of TBI is mainly the injuries about mechanical damage to the tissue, cell membrane and BBB 24 . As a heterogeneous entity, TBI comprise a series of mechanical injury patterns such as extrinsic compression from mass lesion, concussion, diffuse axonal injury 25 , following a range of pathological mechanisms by which neuronal injury can be aroused, such as ischemia, apoptosis 26 , mitochondrial autophagy 27 , cortical spreading depression 28 , edema 29 and microvascular spasm.…”
Section: Traumatic Brain Injury and The Inflammatory Responsementioning
confidence: 99%